Pre-service Teachers’ Beliefs Concerning the Nature of Mathematics and Teaching-learning of Mathematics - Gupta, Charu; Hussain, Jawaid (INDIAN EDUCATIONAL REVIEW, 2018)
The National Curriculum Framework—2005 calls for an epistemological shift in school mathematics, advocating a shift from ‘narrow’ goals to ‘higher’ goals of mathematising. However, to translate this vision into reality, one needs to recognise the significance of the agency of teacher. This necessitates a fundamental re-conceptualisation of teacher preparation and professional development programmes, wherein investigating and challenging the teachers’ beliefs have a crucial role. This study explores pre-service teachers’ beliefs about nature of mathematics and its pedagogy. The paper also attempts at discussing probable consequences of the beliefs held by them for teaching and learning of mathematics. Results show that structural spaces need to be created to engage prospective teachers in the process of reflection, which in turn can help critically inform practice.